Influences of Weld Nugget Shape and Material Gradient on the Shear Strength of Resistance Spot‐Welded Joints - Schuster, Lilia; Olfert, Viktoria; Sherepenko, Oleksii; Fehrenbach, Clemens; Song, Shiyuan; Hein, David; Meschut, Gerson; Biro, Elliot; Münstermann, Sebastian (steel research international)
Resistance spot‐welded joints containing press‐hardened steels are seen to exhibit a fracture mode called total dome failure, where the weld nugget completely separates from one steel sheet along the weld nugget edge. The effect of weld nugget shape and material property gradients is studied based on damage mechanics modeling and experimental validation to shed light on the underlying influencing factors. For a three‐steel‐sheet spot‐welded joint combining DP600 (1.5 mm)–CR1900T (1.0 mm)–CR1900T (1.0 mm), experiments under shear loading reveal that fracture occurs in the DP600 sheet along the weld nugget edge. In subsequent numerical simulation studies with damage mechanics models whose parameters are independently calibrated for every involved material configuration, three variations of the geometrical joint configuration are considered—an approximation of the real joint, one variation with a steeper weld nugget shape, and one variation with a less pronounced gradient between weld nugget material and heat‐affected zone material properties. The results of the finite‐element simulations show that a shallower weld nugget and a more pronounced material gradient lead to a faster increase of plastic strain at the edge of the weld nugget and promote the occurrence of total dome failure.
Keywords: Materials Chemistry; Metals and Alloys; Physical and Theoretical Chemistry; Condensed Matter Physics

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Correction: Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koshukow, Wikentij; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Thermal influence of resistance spot welding on a nearby overmolded thermoplastic–metal joint - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Minch, Steven; Kolbe, Björn (Welding in the World)
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Quasi-In Situ Localized Corrosion of an Additively Manufactured FeCo Alloy in 5 Wt Pct NaCl Solution - Pramanik, Sudipta; Krüger, Jan Tobias; Schaper, Mirko; Hoyer, Kay-Peter (Metallurgical and Materials Transactions A)
Abstract FeCo alloys are important materials used in pumps and motors in the offshore oil and gas drilling industry. These alloys are subjected to marine environments with a high NaCl concentration, therefore, corrosion and catastrophic failure are anticipated. So, the surface dissolution of additively manufactured FeCo samples is investigated in a quasi- in situ manner, in particular, the pitting corrosion in 5.0 wt pct NaCl solution. The local dissolution of the same sample region is monitored after 24, 72, and 168 hours. Here, the formation of rectangular and circular pits of ultra-fine dimensions (less than 0.5 µ m) is observed with increasing immersion time. In addition, the formation of a corrosion-inhibiting surface layer is detected on the sample surface. Surface dissolution leads to a change in the surface structure, however, no change in grain shape or grain size is noticed. The surface topography after local dissolution is correlated to the grain orientation. Quasi- in situ analysis shows the preferential dissolution of high-angle grain boundaries (HAGBs) leading to a change in the fraction of HAGBs and low-angle grain boundaries fraction (LAGBs). For the FeCo sample, a potentiodynamic polarisation test reveals a corrosion potential (E corr ) of − 0.475 V referred to the standard hydrogen electrode (SHE) and a corrosion exchange current density (i corr ) of 0.0848 A/m 2 . Furthermore, quasi- in situ experiments showed that grains oriented along certain crystallographic directions are corroding more compared to other grains leading to a significant decrease in the local surface height. Grains with a plane normal close to the $$\langle {1}00\rangle$$ ⟨ 100 ⟩ direction reveal lower surface dissolution and higher corrosion resistance, whereas planes normal close to the $$\langle {11}0\rangle$$ ⟨ 110 ⟩ direction and the $$\langle {111}\rangle$$ ⟨ 111 ⟩ direction exhibit a higher surface dissolution.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics

Auslegungsmethode zum Kleben höchstfester Stahlwerkstoffe im Landmaschinenbau - Göddecke, Johannes; Göhrs, Tim; Meschut, Gerson; Große Gehling, Manfred (Stahlbau)
Abstract In Konstruktionen des Landmaschinenbaus aus dickeren Blechen (ca. 3–10 mm) findet die Klebtechnik bislang nur wenig Anwendung, obwohl sie in anderen Einsatzgebieten bereits ein etabliertes Fügeverfahren darstellt und viele Vorteile gegenüber anderen Fügeverfahren bietet, da es bisher an Regelwerken bei der Auslegung derartiger Verbindungen fehlt. Ein wesentliches Kriterium bei der Auslegung von Verbindungen im Landmaschinenbau ist die Ermüdungsfestigkeit aufgrund der langen Nutzungsphase der Produkte und der in der Landtechnik vorherrschenden Belastungscharakteristika. Geklebte Verbindungen weisen ein hervorragendes Verhalten bei zyklischer Belastung auf. Die steigenden Anforderungen im Hinblick auf Ressourceneffizienz und Leichtbau führen zu einem Umdenken, da durch den vermehrten Einsatz höherfester Stahlwerkstoffe in Kombination mit der Klebtechnik dieses als umsetzbar erscheint. Ziel ist die Entwicklung einer Methode zur Auslegung geklebter Verbindungen in Konstruktionen mit höherfesten Stahlwerkstoffen in Anlehnung an die FKM‐Richtlinie. Die betriebsrelevanten Beanspruchungen der Landtechnik werden analysiert und an speziellen Probekörpern untersucht. Dabei werden sowohl die mechanischen, thermischen und medialen Einflussfaktoren als auch der Einfluss der Klebfugengeometrie und von Betriebslastenkollektiven untersucht. Die Erkenntnisse werden in einer KMU‐relevanten Vorgehensweise zur Ermittlung von Abminderungsfaktoren zusammengefasst, wodurch die Auslegung der Bauteilfestigkeit sowohl statisch als auch dynamisch möglich ist.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials; Building and Construction; Civil and Structural Engineering

Influence of hydrogel coatings on corrosion and fatigue of iron in simulated body fluid - Huang, Jingyuan; Voigt, Markus; Wackenrohr, Steffen; Ebbert, Christoph; Keller, Adrian; Maier, Hans Jürgen; Grundmeier, Guido (Materials and Corrosion)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry; Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; Mechanical Engineering; Mechanics of Materials; Environmental Chemistry

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

A comparison of heuristic, statistical, and machine learning methods for heated tool butt welding of two different materials - Gevers, Karina; Tornede, Alexander; Wever, Marcel Dominik; Schöppner, Volker; Hüllermeier, Eyke (Welding in the World)
Abstract Heated tool butt welding is a method often used for joining thermoplastics, especially when the components are made out of different materials. The quality of the connection between the components crucially depends on a suitable choice of the parameters of the welding process, such as heating time, temperature, and the precise way how the parts are then welded. Moreover, when different materials are to be joined, the parameter values need to be tailored to the specifics of the respective material. To this end, in this paper, three approaches to tailor the parameter values to optimize the quality of the connection are compared: a heuristic by Potente, statistical experimental design, and Bayesian optimization. With the suitability for practice in mind, a series of experiments are carried out with these approaches, and their capabilities of proposing well-performing parameter values are investigated. As a result, Bayesian optimization is found to yield peak performance, but the costs for optimization are substantial. In contrast, the Potente heuristic does not require any experimentation and recommends parameter values with competitive quality.
Keywords: Metals and Alloys; Mechanical Engineering; Mechanics of Materials